Capsaicin Induces Apoptosis in KSHV-Positive Primary Effusion Lymphoma by Suppressing ERK and p38 MAPK Signaling and IL-6 Expression - Moriguchi, Misato; Watanabe, Tadashi; Kadota, Ayano; Fujimuro, Masahiro (Frontiers in Oncology, 2019)
Primary effusion lymphoma (PEL) is defined as a rare subtype of non-Hodgkin’s B-cell lymphoma which is caused by Kaposi’s sarcoma-associated herpesvirus (KSHV) in immunosuppressed patients. PEL is an aggressive lymphoma and is frequently resistant to conventional chemotherapies. Therefore, it is critical to investigate novel therapeutic options for PEL. Capsaicin is a pungent component of chili pepper and possesses unique pharmacological effects, such as pain relief, anti-microbial and anti-cancer properties. Here, we demonstrate that capsaicin markedly inhibited the growth of KSHV-infected PEL cells by inhibiting ERK, p38 MAPK and expression hIL-6, which are known to contribute to PEL growth and survival. The underlying mechanism of action by capsaicin was through the inhibition of ERK and p38 MAPK phosphorylation and signaling that affected hIL-6 expression. As a result, capsaicin induced apoptosis in PEL cells in a caspase-9 dependent manner. In line with these results, ERK (U0126) and p38 MAPK (SB203580) specific signaling inhibitors suppressed hIL-6 expression and attenuated cell growth in PEL cells. Furthermore, the addition of hIL-6 neutralizing antibody to culture medium suppressed the growth of PEL cells. We also demonstrate that capsaicin suppressed PEL cell growth in the absence of nascent viral replication. Finally, we confirmed ex vivo treatment of capsaicin attenuated PEL development in SCID mice. Taken together, capsaicin could represent a novel therapeutic drug candidate against PEL without the risk of de novo KSHV infection.